Acquiring Reading and Writing Skills among Beginner Learners of Arabic Language, An Applied Analytical Study of the First and Second Books of the University of Jordan’s Arabic Curriculum for Non-native Speakers - Yunis, Izdihar; Dajani, Basma (Dirasat: Human and Social Sciences, 2022)
This applied study identifies the common mistakes among beginner learners of the non-native Arabic language in reading and writing skills. It measures the two skills in the progress of those learners according to the descriptive-analytical method. It answers the following questions: What are the types of errors in reading among non-native Arabic learners at the beginner level? What are the types of errors in writing, and their proportion among non-native Arabic learners at the beginner level? The sample of this study consisted of 50 students who studied at the beginner level at the University of Jordan before the Arab Spring. Two tests were conducted for them in reading and writing skills to obtain consistent results. The first test measured verbal reading skills, and the second test measured writing. The study analyzed patterns of writing errors among beginners of non-native Arabic language learners, revealed their frequency and percentages, and highlighted their diversity among three main sections: spelling errors, a synthetic, and a third semantic.